2022
DOI: 10.1200/op.21.00719
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Disparities and Factors Associated With the Decision to Decline Chemotherapy in Breast Cancer

Abstract: PURPOSE: Social determinants of health have been linked to treatment-related disparities in breast cancer. We analyzed data from a large national registry to explore factors related to accepting or declining recommended chemotherapy and whether patients' decisions vary geographically across the United States. METHODS: We used the National Cancer Database to study treatment decision making in patients with advanced breast cancer (American Joint Committee on Cancer clinical stage III-IV) between 2004 and 2017. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Additionally, the highest refusal rates were found in the New England region, followed by the Pacific region and the West North Central region of the US. A previous NCDB-based study on stage III and stage IV patients with breast cancer also reported comparable findings, with the New England region having the highest likelihood of patient refusal of recommended chemotherapy [ 13 ]. While the NCDB does not document the specific causes for refusal, several reasons could be behind these observations.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Additionally, the highest refusal rates were found in the New England region, followed by the Pacific region and the West North Central region of the US. A previous NCDB-based study on stage III and stage IV patients with breast cancer also reported comparable findings, with the New England region having the highest likelihood of patient refusal of recommended chemotherapy [ 13 ]. While the NCDB does not document the specific causes for refusal, several reasons could be behind these observations.…”
Section: Discussionmentioning
confidence: 57%
“…Factors that lead patients to select or refuse treatments are complex and varied [ 8 , 9 ]. Beyond the physicians’ recommendation, patients’ selection of therapy may be influenced by health literacy and understanding [ 10 ], financial toxicity [ 11 ], and other sociodemographic and cultural factors [ 12 , 13 ]. Additionally, fear of unpleasant side effects from cancer treatment could be one of the most motivating factors to find alternative treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…For BC, several analyses have reported similar sociodemographic and clinical factors associated with treatment declination in this patient population. 7,10,[18][19][20][21][22] However, these studies focused on either chemotherapy or surgery only or the associations of treatment decisions with mortality, and most of them did not evaluate the pattern and long-term trends associated with treatment declination among patients with BC. Although a few studies have assessed racial and ethnic disparities in declination of surgery or chemotherapy, they largely focused on Black and Hispanic patients, and, to a lesser extent, Asian patients, 10,18,19,21 and 2 analyses included only White women.…”
Section: Introductionmentioning
confidence: 99%
“…7,10,[18][19][20][21][22] However, these studies focused on either chemotherapy or surgery only or the associations of treatment decisions with mortality, and most of them did not evaluate the pattern and long-term trends associated with treatment declination among patients with BC. Although a few studies have assessed racial and ethnic disparities in declination of surgery or chemotherapy, they largely focused on Black and Hispanic patients, and, to a lesser extent, Asian patients, 10,18,19,21 and 2 analyses included only White women. 4,7 There remain gaps in the literature regarding national trends in declination of treatment recommendations, racial and ethnic disparities, sociodemographic and clinicopathologic characteristics associated with treatment declination, and the implication of treatment declination for overall survival (OS) among patients with BC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation